Carbon monoxide inhibits sprouting angiogenesis and vascular endothelial growth factor receptor-2 phosphorylation - Ahmad, Shakil; Hewett, Peter W.; Fujisawa, Takeshi; Sissaoui, Samir; Cai, Meng; Gueron, Geraldine; Al-Ani, Bahjat; Cudmore, Melissa; Ahmed, Faraz S.; Wong, Michael K. K.; Wegiel, Barbara; Otterbein, Leo E.; Vítek, Libor; Ramma, Wenda; Wang, Keqing; Ahmed, Asif (Thrombosis and Haemostasis, 2015)
Carbon monoxide (CO) is a gaseous autacoid known to positively regulate vascular tone; however, its role in angiogenesis is unknown. The aim of this study was to investigate the effect of CO on angiogenesis and vascular endothelial growth factor (VEGF) receptor-2 phosphorylation. Human umbilical vein endothelial cells (HUVECs) were cultured on growth factor-reduced Matrigel and treated with a CO-releasing molecule (CORM-2) or exposed to CO gas (250 ppm). Here, we report the surprising finding that exposure to CO inhibits vascular endothelial growth factor (VEGF)-induced endothelial cell actin reorganisation, cell proliferation, migration and capillary-like tube formation. Similarly, CO suppressed VEGF-mediated phosphorylation of VEGFR-2 at tyrosine residue 1175 and 1214 and basic fibroblast growth factor- (FGF-2) and VEGF-mediated Akt phosphorylation. Consistent with these data, mice exposed to 250 ppm CO (1h/day for 14 days) exhibited a marked decrease in FGF-2-induced Matrigel plug angiogenesis (p<0.05). These data establish a new biological function for CO in angiogenesis and point to a potential therapeutic use for CO as an anti-angiogenic agent in tumour suppression.
Keywords: Carbon monoxide; vascular endothelial growth factor; angiogenesis; endothelial cells; vascular endothelial growth factor receptor-2